2014
DOI: 10.1590/1676-060320140615183049
|View full text |Cite
|
Sign up to set email alerts
|

Benthic marine algae from the insular areas of Paraná, Brazil: new database to support the conservation of marine ecosystems

Abstract: This study describes the diversity of benthic marine algae from insular areas of the southern Brazilian coast. Algal samples were collected between 2006 and 2010 during the winter and the summer seasons at three sites in the coastal waters of Paraná , Brazil: Ilha do Mel, Currais Archipelago and Ilha do Farol. The samples were collected along parallel transects on the coast. In this survey, Paraná marine phycoflora comprised 139 taxa (90 Rhodophyta, 27 Chlorophyta and 22 Phaeophyceae). Fifty-two species repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
4
0
3
Order By: Relevance
“…Taxon oriented inventories by specialists are also mandatory for a comprehensive biodiversity survey. For example, a large algal richness was found in a recent study, which found 101 taxa in the Currais Islands (Pellizzari et al 2014). The coast of Paraná is in the area of influence of the southern convergence between the cold Malvinas/Falklands current from the south and the warm Brazilian current from the north (Campos et al 1996, Fernandes & Brandini 2004, and so the communities are expected to include species from both temperate and tropical waters.…”
Section: Dzup-symp52mentioning
confidence: 98%
See 1 more Smart Citation
“…Taxon oriented inventories by specialists are also mandatory for a comprehensive biodiversity survey. For example, a large algal richness was found in a recent study, which found 101 taxa in the Currais Islands (Pellizzari et al 2014). The coast of Paraná is in the area of influence of the southern convergence between the cold Malvinas/Falklands current from the south and the warm Brazilian current from the north (Campos et al 1996, Fernandes & Brandini 2004, and so the communities are expected to include species from both temperate and tropical waters.…”
Section: Dzup-symp52mentioning
confidence: 98%
“…Only one study examined the soft bottom infauna (Lorenzi & Borzone 2009), three examined benthic invertebrates on hard substrates, one of ascidians (Rocha & Faria 2005) and two experimental studies on temporal colonization of artificial substrates near the islands (Brandini & Silva 2011, Bumbeer & Rocha 2012. Since the creation of the MPA, there has been only one study of marine biota, which examined the algal community (Pellizzari et al 2014). On a larger scale, invertebrates of hard substrates are very poorly studied along the entire coast of Paraná, and is a major gap in the understanding of species distributions in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, a unidade operacional Cianobactéria apresentou diferenças no RPM entre os períodos estudados, uma vez que foi encontrada em apenas um período do ano (inverno 2014). Nesta faixa, não foram descritas espécies bioindicadoras (PELLIZZARI et. al., 2014) para o monitoramento nos trabalhos realizados nas ecorregiões Southeastern Brazil e Rio Grande (SPALDING et al, 2007).…”
Section: Faixa Superiorunclassified
“…Na faixa inferior, as unidades operacionais A. beauvoisii e Sargassum vulgare, as quais estão presentes praticamente durante o ano todo, sendo a primeira conspícua e a segunda observada ao longo do ano (PAULA, 1984;AMADO-FILHO et al, 2003ALMADA et al, 2008) também foram observadas na região inferior da faixa intermediária. Tais espécies podem ser utilizadas como unidades bioindicadoras de variação sazonal e monitoramento (PELLIZZARI et al, 2014), uma vez que a maioria das populações intermareais de ambientes tropicais são mais constantes no tempo e espaço que suas equivalentes em ambiente temperado (LUBCHENCO et al, 1984).…”
Section: Faixa Inferiorunclassified
See 1 more Smart Citation